Contact guidance for cardiac tissue engineering using 3D bioprinted gelatin patterned hydrogel - Tijore, Ajay (2019)
Here, we have developed a 3D bioprinted microchanneled gelatin hydrogel that promotes human mesenchymal stem cell (hMSC) myocardial commitment and supports native cardiomyocytes(CMs) contractile functionality. Firstly, we studied the effect of bioprinted microchanneled hydrogel on the alignment, elongation, and differentiation of hMSC. Notably, the cells displayed well defined F-actin anisotropy and elongated morphology on the microchanneled hydrogel, hence showing the effects of topographical control over cell behavior. Furthermore, the aligned stem cells showed myocardial lineage commitment, as detected using mature cardiac markers. The fluorescence-activated cell sorting analysis also confirmed a significant increase in the commitment towards myocardial tissue lineage. Moreover, seeded CMs were found to be more aligned and demonstrated synchronized beating on microchanneled hydrogel as compared to the unpatterned hydrogel. Overall, our study proved that microchanneled hydrogel scaffold produced by 3D bioprinting induces myocardial differentiation of stem cells as well as supports CMs growth and contractility. Applications of this approach may be beneficial for generating in vitro cardiac model systems to physiological and cardiotoxicity studies as well asin vivo generating custom designed cell impregnated constructs for tissue engineering and regenerative medicine applications.